2015
DOI: 10.1007/s13224-015-0712-y
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Congenital Adrenal Hyperplasia in India: What Do We Need to Watch Out for?

Abstract: Background Congenital Adrenal Hyperplasia (CAH) is a disorder-an ideal candidate to deserve newborn screening. CAH accounts for a significant mortality and morbidity in India, and its awareness among obstetricians should be treated as highly important to prevent the problem.Purpose of the Study It is very important for a country like India as the incidence of CAH is reasonably high justifying screening program. However, there are simple logistics that need to be followed, and the treating physicians need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Newborn screening for CAH began with the development of a radioimmunoassay by Pang et al, 1977 [ 10 ] measuring 17 α-hydroxyprogesterone(17OHP) using blood on microfilter paper. Since then, worldwide CAH screening or pilot studies have ensued [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Newborn screening for CAH is aimed at identifying newborns with SWCAH promptly to prevent a life threatening adrenal crisis, thus reducing morbidity and mortality in affected individuals [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Newborn screening for CAH began with the development of a radioimmunoassay by Pang et al, 1977 [ 10 ] measuring 17 α-hydroxyprogesterone(17OHP) using blood on microfilter paper. Since then, worldwide CAH screening or pilot studies have ensued [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Newborn screening for CAH is aimed at identifying newborns with SWCAH promptly to prevent a life threatening adrenal crisis, thus reducing morbidity and mortality in affected individuals [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In India, absence of neonatal screening, CAH diagnosis is missed in male gender and recognized only in the later part of life when signs of adrenal insufficiency like hyperpigmentation, hypotension, or precocious pseudo puberty appear. [ 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…The study showed marked regional differences, with the prevalence being 1 in 2036 in Chennai, 1 in 7608 in Delhi and 1 in 9983 in Mumbai [ 23 ]. Other recent studies from India, found the incidence of CAH to be 1 in 2800 in South India [ 24 ] and 1:6334 in North India [ 4 ]. The differences in incidence of CAH reported from India may be because of the variations in technique used, different cut-offs, different disorder definition and/or different populations screened.…”
Section: Disease Burden In India and Need Of Nbsmentioning
confidence: 99%